Shaping Curriculum in State Islamic Religious Universities (PTKIN) to Match the Job Market - Annisa, Arna Asna; Puspita, Rosana Eri (UIII Press, 2022)
The high unemployment rate at the graduate level is a matter of concern. State Islamic Religious Universities (PTKIN) as a producer of scholars who have core religious values must be able to provide solutions to reduce the unemployment rate in Indonesia. The purpose of this study is to analyze how the curriculum implemented at PTKIN compares to the experience of PTKIN alumni at work to find out whether the needs of alumni have been met during lectures. The focus of analysis in this research is PTKIN campuses in Indonesia. The samples in this study were representatives of PTKIN with various accreditation scores of Superior (UIN Sunan Kalijaga Yogyakarta), A (UIN Walisongo Semarang), and B (IAIN Salatiga) as well as alumni from each PTKIN. Through qualitative data analysis using Atlas t.i, it was found that there is still a gap between the curriculum that applies at PTKIN and the needs of the job market. Even though academic tools at universities are already available, alumni feel they have to learn on their own to gain the competencies needed according to the job positions they have. This finding provides a reference for the Ministry of Religion, PTKIN, and related agencies to produce a curriculum that better accommodates students’ competencies needed to do their jobs.